2016
DOI: 10.1002/etc.3469
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress response of the aquatic macrophyte Hydrilla verticillata exposed to TiO2 nanoparticles

Abstract: The present study investigated the effects of titanium dioxide nanoparticles (TiO -NPs) on the oxidative stress response in Hydrilla verticillata. Macrophytes were exposed to different concentrations of TiO -NPs (0 mg/L, 0.01 mg/L, 0.1 mg/L, 1 mg/L, and 10 mg/L) for 24 h, based on currently predicted levels of nano-TiO in surface waters. In addition, TiO -NPs with varying crystalline status were used to assess the potential influence of crystalline phases on oxidative stress responses. The level of hydrogen pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 41 publications
0
17
0
3
Order By: Relevance
“…Among these, proline, compatible solute, besides its contribution to osmotic adjustment, protects macromolecules in stress conditions and can act as a radical scavenger (Hayat et al 2012 conditions. Both decrease and increase in the activity of these enzymes have been reported in the presence of cadmium (Li et al 2013;Balestri et al 2014a;Irfan et al 2014) or TiO2 NPs (Lei et al 2008;Foltete et al 2011;Ruffini Castiglione et al 2014Okupnik and Pflugmacher 2016).…”
Section: Oxidative Stress and Antioxidant Responsementioning
confidence: 96%
“…Among these, proline, compatible solute, besides its contribution to osmotic adjustment, protects macromolecules in stress conditions and can act as a radical scavenger (Hayat et al 2012 conditions. Both decrease and increase in the activity of these enzymes have been reported in the presence of cadmium (Li et al 2013;Balestri et al 2014a;Irfan et al 2014) or TiO2 NPs (Lei et al 2008;Foltete et al 2011;Ruffini Castiglione et al 2014Okupnik and Pflugmacher 2016).…”
Section: Oxidative Stress and Antioxidant Responsementioning
confidence: 96%
“…Tripathi et al ( 2015 ) have studied that Silica nanoparticle was able to alleviate chromium (VI) phytotoxicity in Pisum sativum (L.) seedlings (Tripathi et al, 2015 ). Several studies on the impact of metal and metal oxide nanoparticles on plant have shown a toxic impact on plants, whereas few studies also indicated their beneficial role in the form of enhancing plant growth parameters and productivity (Castiglione et al, 2011 ; Clément et al, 2013 ; Dimkpa et al, 2013 ; Jaberzadeh et al, 2013 ; Jiang et al, 2014 ; Rafique et al, 2014 ; Raliya et al, 2015 ; Okupnik and Pflugmacher, 2016 ; Cvjetko et al, 2017 ; Tripathi et al, 2017 ).…”
Section: Effect Of Nanoparticles On Plantsmentioning
confidence: 99%
“…It is considered that the imbalance in plant synthesis of antioxidants and quenching system may cause oxidative damage that results in the production of reactive oxygen species (ROS) and ultimately affect the physiological functioning and eventually leads to cell death and decline in the crop yield [18][19][20]. For protecting the plant from the dangerous effects of the ROS, the defense system against oxidative damage is activated by enzymatic (superoxide dismutase, peroxidase and catalase) and non-enzymatic antioxidants such as phenolic compounds, proline and flavonoids [21].…”
Section: Introductionmentioning
confidence: 99%